Модифікування енергетичного стану нанопористого біовуглецю для адсорбентів і електродів суперконденсаторів - Садова, Марія Михайлівна (Національний університет "Львівська політехніка", 2018)
В дисертації досліджено структуру, поляризаційні та сорбційні властивості нанопористого біовуглецю та проведена його модифікація методами ультразвукового впливу у докавітаційному та кавітаційному режимах. Показано ефективність використання нанопористих вуглецевих матеріалів як адсорбентів та активного матеріалу електродів суперконденсаторів. Проведено імпедансний аналіз активованих вуглецевих матеріалів до та після ультразвукового опромінення, який показує зсув рівня Фермі в область з більшою густиною делокалізованих електронних станів і, відповідно, зростання питомої ємності біовуглеців. Для синтезованих біовуглеців встановлено наявність асиметризації вольт-фарадних залежностей при додатній і від’ємній поляризаціях. Встановлено, що ультразвукове опромінення у кавітаційному режимі збільшує сорбційну здатність активованого вугілля до широкого спектру нафтопродуктів. Розроблено методику розрахунку питомої площі поверхні біовуглеців на основі аналізу ізотерм адсорбції метиленового синього з врахуванням гідрофільності поверхні вугілля. В диссертации исследованы структура, поляризационные и сорбционные свойства нанопористого био-углерода и проведена его модификация методами ультразвукового воздействия в докавитационном и кавитационном режимах. Показано эффективность использования нанопористых углеродных материалов как адсорбентов и активного материала электродов суперконденсаторов. Проведено импедансный анализ активированных углеродных материалов до и после ультразвукового облучения, который показывает смещение уровня Ферми в область с большей плотностью делокализованных электронных состояний и, соответственно, рост удельной емкости био-углерода. Для синтезированных био-углеродов установлено наличие асиметризации вольт-фарадных зависимостей при положительной и отрицательной поляризациях. Установлено, что ультразвуковое облучение в кавитационном режиме увеличивает сорбционную способность активированного угля к широкому спектру нефтепродуктов. Разработана методика расчета удельной площади поверхности биовуглецив на основе анализа изотерм адсорбции метиленового синего с учетом гидрофильности поверхности угля. В диссертации исследованы структура, поляризационные и сорбционные свойства нанопористого био-углерода и проведена его модификация методами ультразвукового воздействия в докавитационном и кавитационном режимах. Показано эффективность использования нанопористых углеродных материалов как адсорбентов и активного материала электродов суперконденсаторов. Проведено импедансный анализ активированных углеродных материалов до и после ультразвукового облучения, который показывает смещение уровня Ферми в область с большей плотностью делокализованных электронных состояний и, соответственно, рост удельной емкости био-углерода. Для синтезированных био-углеродов установлено наличие асиметризации вольт-фарадных зависимостей при положительной и отрицательной поляризациях. Установлено, что ультразвуковое облучение в кавитационном режиме увеличивает сорбционную способность активированного угля к широкому спектру нефтепродуктов. Разработана методика расчета удельной площади поверхности био-вуглецив на основе анализа изотерм адсорбции метиленового синего с учетом гидрофильности поверхности угля. The dissertation investigates the structure, polarization and sorption properties of nanoporous bio-carbon, and modifies it by methods of ultrasonic influence in the precavitation and cavitational regimes. It is shown on the basis of the analysis of X-ray diffraction data of the investigated materials, that all of them are characterized by a microheterogeneous structure, which is manifested in the formation of graphite-like and graphene nanocrystals distributed in the amorphous phase. It should be noted that the dominant contribution (from 75 to 82%) in the crystalline component is given by threedimensional graphite-like crystallites. It has been established that ultrasound irradiation in precavitational and cavitational regimes of synthesized bio-carbons not only efficiently shreds carbon particles, but also reduces the total number of surface groups. At the same time there is an increase of hydrophilicity without significant changes in the porous structure. Such changes improve the coefficient of use of the active surface of carbon when it is used as an active material of electrodes of super-capacitors by increasing its specific capacity. An impedance analysis of activated carbon materials before and after ultrasound irradiation was performed, which shows a shift of the Fermi level to a region with a higher density of delocalized electronic states. This is the reason for the release of the Helmholtz layer capacity by increasing the capacity of the layer of the spatial charge region in a carbonaceous material. Such a redistribution of the values of the capacities forming the double electric layer, after the influence of ultrasound improves the characteristics of supercapacitors, and in particular, increases their specific capacity. For synthesized carbons, the presence of asymmetrization of the volt-farad dependencies with positive and negative polarizations has been established. At the same time, the strong growth of the specific capacity in the anode region of potentials up to 163 F/g, 172 F/g and 214 F/g, respectively, for activated charcoal grade BAU-A, and synthesized from beet pulp and corn stalks, provides them no alternative efficacy when used as the negative electrode asymmetric ultracapacitor. It has been established that ultrasound irradiation in cavitation mode increases the sorption ability of activated carbon to a wide range of petroleum products. Particularly this effect becomes noticeable in the absorption of diesel fuel with activated carbon from corn stems - absorption increases by 50% compared with the absorption with unmodified activated carbon. It has been established that the isotherms of adsorption of methylene blue from aqueous solutions for all investigated types of activated carbon can be described as isotherms of type ІІ. This type of isotherm is modeled by the Langmuir model. On the basis of modeling results, specific surface area was calculated based on the magnitude of the amount of absorbed dye. It is established that the method of determining the specific surface area of different types of coal by the absorption of methylene blue from aqueous solutions is in good agreement with the results obtained with the standard nitrogen adsorption method, taking into account the hydrophilic properties of the surface of activated carbon. This method can be proposed as a simple method for evaluating the surface area of carbon sorbents, since it does not require complex equipment and is fast enough.
Модифицирование энергетического состояния нанопористого био-углерода для адсорбентов и электродов суперконденсаторов
Modification of the energy state of a nanoporous bio-carbon for adsorbents and supercapacitors electric drives
Keywords: активоване вугілля; ультразвукове опромінення; поверхневі групи; подвійний електричний шар; питома поверхня; гідрофільність; активированный уголь; ультразвуковое облучение; поверхностные группы; двойной электрический слой; удельная поверхность; гидрофильность; activated carbon; ultrasound irradiation; surface groups; electric double layer; specific capacity; hydrophilicity; 538.971:621.311.6:541.136.88